EDUCATIONAL SERVICES AS AN ECONOMIC INDICATOR: THE ROLE OF THE HUMAN FACTOR - Mansurova Muzaffarra Makhsudovna (TADQIQOTLAR, 2026)
Abstract. The article examines the importance of educational services as a significant economic indicator and a factor in the formation of human capital. It substantiates that, under modern conditions, education should be considered not only as an element of the social sphere, but also as a strategic resource for the socio- economic development of the state. Special attention is paid to the role of the human factor in the system of educational services, including students’ motivation, teaching quality, social environment, and individual characteristics. Using the Republic of Uzbekistan as an example, the article analyzes selected indicators of the development of the education sector, including education expenditure, literacy rate, the number of higher education institutions, as well as the volume and dynamics of educational services. The article concludes that the effectiveness of educational services depends not only on quantitative indicators and the level of financing, but also on the ability of the education system to form high-quality human capital that meets the needs of the modern economy.